2009
DOI: 10.1053/j.gastro.2009.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell Functional Dichotomy in Chronic Hepatitis B and Chronic Hepatitis C Virus Infections

Abstract: These findings provide evidence for a functional dichotomy in patients with chronic HBV and HCV infections, featuring conserved or enhanced cytolytic activity and dysfunctional cytokine production, which may contribute to virus persistence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

40
401
8
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(455 citation statements)
references
References 53 publications
40
401
8
1
Order By: Relevance
“…81 Notably, persistent HBV or HCV infection, which is the main risk factor for HCC, has been shown to influence NK cell phenotype, especially by increasing expression of inhibitory receptors and reducing expression of activating receptors (Table 3). [82][83][84][85][86][87][88][89] In one study, NK cells from chronic HCV patients had a significantly reduced expression of NKp46 and NKp30 and an increased expression of NKG2A compared with NK cells from healthy and HBV infected subjects. 88 Our group recently found a higher percentage of NKG2A 1 NK cells in peripheral blood from patients with active CHB patients than from patients with inactive CHB or from control patients.…”
Section: Downregulated Activating Receptorsmentioning
confidence: 99%
“…81 Notably, persistent HBV or HCV infection, which is the main risk factor for HCC, has been shown to influence NK cell phenotype, especially by increasing expression of inhibitory receptors and reducing expression of activating receptors (Table 3). [82][83][84][85][86][87][88][89] In one study, NK cells from chronic HCV patients had a significantly reduced expression of NKp46 and NKp30 and an increased expression of NKG2A compared with NK cells from healthy and HBV infected subjects. 88 Our group recently found a higher percentage of NKG2A 1 NK cells in peripheral blood from patients with active CHB patients than from patients with inactive CHB or from control patients.…”
Section: Downregulated Activating Receptorsmentioning
confidence: 99%
“…Many research groups have shown that NK cells in patients with chronic hepatitis B become defective in terms of producing IFN-c with preserved cytotoxic activity [31][32][33][34][35]. Furthermore, TRAIL (TNF-related apoptosis-inducing ligand)-expressing NK cells eliminate HBV-specific T cells which highly express the TRAIL death receptor TRAIL-R2 [36].…”
Section: Nk Cells and Dcs In Chronic Hbv Infectionmentioning
confidence: 99%
“…As NK-cells act as rheostats modulating antiviral T-cells, interference with NK-cell function may also contribute to viral persistence (Welsh & Waggoner, 2013). In humans infected with the closely related HCV, NK-cell production of IFN-c and TNF-a is suppressed (Ahlenstiel et al, 2010;Oliviero et al, 2009;Peppa et al, 2010), whilst cytotoxicity and degranulation is increased (Ahlenstiel et al, 2010; De Maria et al, 2007). Further study to examine the effect of HPgV infection on NK-cell function is needed, and these studies may identify critical and novel host immunomodulatory mechanisms pertinent to viral persistence.…”
mentioning
confidence: 99%